2016
DOI: 10.1186/s12863-016-0464-4
|View full text |Cite
|
Sign up to set email alerts
|

Haploid yeast cells undergo a reversible phenotypic switch associated with chromosome II copy number

Abstract: Background SUP35 and SUP45 are essential genes encoding polypeptide chain release factors. However, mutants for these genes may be viable but display pleiotropic phenotypes which include, but are not limited to, nonsense suppressor phenotype due to translation termination defect. [PSI +] prion formation is another Sup35p-associated mechanism leading to nonsense suppression through decreased availability of functional Sup35p. [PSI +] differs from genuine sup35 mutations by the possibility of its elimination and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Recent years have seen a huge amount of published S. cerevisiae genome sequences, which have revealed a high level of genetic diversity, phenotypic variation and copy number variation in this species [ 24 , 37 , 38 , 39 , 40 ]. In some of the works, it has been shown that structural changes in the genome (such as CNVs) may have an adaptive role (e.g., [ 38 ]), however, it remains unclear if selective pressure may actively facilitate the accumulation of genetic changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent years have seen a huge amount of published S. cerevisiae genome sequences, which have revealed a high level of genetic diversity, phenotypic variation and copy number variation in this species [ 24 , 37 , 38 , 39 , 40 ]. In some of the works, it has been shown that structural changes in the genome (such as CNVs) may have an adaptive role (e.g., [ 38 ]), however, it remains unclear if selective pressure may actively facilitate the accumulation of genetic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, several similar observations of aneuploidies associated with nonsense suppression and release factor genes have been reported. These include a phenomenon of reversible nonsense suppressor phenotype switching due to chromosome II copy number observed in the presence of missense mutations in the SUP35 and SUP45 genes [ 40 ]. This case is reminiscent of the chromosome II disomy, which we observed in this work in the sup35-203 mutant.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the chromosome I disomy may potentially alleviate this process by increasing ade1-14 levels, which was previously found to compensate for the growth defects of the strains with the same genotype on a media without adenine [43]. Notably, the aneuploidy was demonstrated to be associated with the formation of different non-chromosomal determinants affecting the translation termination efficiency, like [ ISP + ] (initially described as a prion form of the transcriptional regulator Sfp1 [11] and later connected with the chromosome II copy number [69]), as well as the [ ASP + ] (chromosome VIII disomy [70]). Probably, the prion formation by several proteins regulating key biological processes could induce genome instability in a few fractions of cells that are inherited by progeny under selective pressure and determine adaptive phenotypic traits like resistance to poisonous compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Custom 8x15k design (AMID 028943) Agilent arrays were used. CGH analysis was carried out as described previously ( Drozdova et al 2016a ). The data were processed with the CGH-Miner Excel add-in ( Wang et al, 2005 ) and a custom R function based on the clac package.…”
Section: Methodsmentioning
confidence: 99%